Letter from the Director of the Military Hospital, Ucles (copy) - Landa, Ramon G.
042-0017-001 LETTER FROM THE DIRECTOR OF THE MILITARY HOSPITAL, UCLES. 4th July 1938. Dear Friends, Taking the advantage of Johnnie Hall coming to England I am giving you some impressions about this hospital, for which you have done so much. In the first place I must tell you that many former deficiencies have been corrected. From the Hygienic point of view we have managed to get a fine bathroom with five baths working, it has also fourteen wash basins and six showers and can be taken as an example as the best fitted Spanish war hospital. Next to these rooms are the barber shop and a very good clothing store, all of which is well organised and function very well. We have constructed a new group of lavatories and have improved those already in existence. The evacuation of sewage and cleaning of these lavatories before the sewage goes into the river is achieved through the hospital then to a perfect drainage system using septic pits. We have not been able to do this in the other part of the building for military reasons, which you all know which have made made transport of the material which we needed very difficult from Barcelona. The "quiroganos" are completely furnished as well as the new orthoedic services. We have various places, well fitted out, where the wounded men are received who are to go into the hospital and similarly they are evacuated to these places when they are cured or are being transferred to other hospitals. We have installed an electric pump which brings water to the hospital in more than sufficient quantities for all our services. Some time ago we finished constructing a theatre where we attend to the culture of the wounded and to distract them. We also have a school where we teach the illiterate and also those who want to improve their studies. We are very satisfied with the work of the English nurses who have worked always to help improve the knowledge of our own nurses, so that they can give better attention to the wounded and keep them cleaner and things have improved very much in this way. Comrade Frank Ayres who was in charge of the mission in Ucles does not live here now. He came to see us the other day and told us that his other work obliged him to reside in Valencia but he will come to Ucles periodically every fifteen days to attend to the business of the mission in the hospital. To this comrade we have handed over the "liquidation" (i,e. accounts etc) of the quantity of 100,000 pesetas which up to now the mission has given us. He gave us another 5,000 pesetas on the 2nd of this month (July) and has promised to give us further economic support which we need very much in order to carry out the work we have in view. The work to be carried out and the budget for the same has been handed over to this comrade and it amounts to 25,000 pesetas. This work will represent the finishing of the hospital and assist in the termination of the hygienic improvements to which I have referred making a new ward for 100 beds, a garage and various repairs. After that we shall be able to say that the hospital is completed. We believe it wise to give this news because since last December we did not do it and at the same time we want to acknowledge our debt of gratitude to your Committee for its fine help to the Spanish people which help will always remain evident in this old monastery. Yours fraternally and for the anti-fascist cause. - (signed) Ramon G. Landa. 292/946/42/17